The Correlation between Mothers’ Knowledge and Attitude following Posyandu and Weight Gain in Children Aged 2-3 Years in Sawah Besar Village, Gayamsari District of Semarang - Fitriyani, Anis; Indrawati, Nuke Devi (Fakultas Kedokteran; Universitas Islam Sultan Agung (UNISSULA), 2013)
Minister of health decree No. 1457/ MENKES/ SK/ 2003 states that the minimum service standard in health sector for growth monitoring activitiesat integrated service post (Posyandu) in the office of Semarang Municipality targeted 80.17% children gain wight. But the gaining weight infants in the District Gayamsari were 72.09%.The study seeks to know the corelation between the level of knowledge and atittude of mothers following Posyandu and weight gain in children aged 2-3 years in the Sawah Besar Village Gayamsari District of Semarang. This study was a cross-sectional study a using a questionner. A sample were 87 mothers who had children aged 2-3 years in the Village and following the Sawah Besar Posyandu from total population 690 children were selected using a proportionate random stratified sampling method. The finding indicates that 46 % mothers had enough knowledge 48.3% mothers showed ‘not good’ attitute. Most of the children (59.8%) did not gain weight. There was a correlation between the mothers’ level of knowledge and attitute and the weight gain in children aged 2-3 years.